Electrochemical Formation Mechanism of Microdroplets on Pure Iron - Tang, Xiao; Li, Juanjuan; Wu, Yuan; Hu, Hao; Ma, Chao Ran; Li, Yan; Fan, Haiming (Frontiers in Chemistry, 2021)
The electrochemical formation mechanism of microdroplets formed around a primary droplet of 3.5% NaCl solution on an iron-plated film was investigated by quartz crystal microbalance (QCM) and concentric three-electrode array (CTEA) measurements. During the initial stage, the microdroplets mainly originate from evaporation owing to cathodic polarization and electric current of the localized corrosion cell under the primary droplet. The maximal electrochemical potential difference between the anode and cathode was measured to be 0.36 V and acted as the driving force for the formation of microdroplets. The maximums of anodic and cathodic electric current density of pure iron under the NaCl droplet are 764 and −152 μA/cm2, respectively. Propagation of microdroplets in the developing stage attributes to horizontal movement of the electrolyte, water evaporation, and recondensation from primary and capillary condensation from moist air. The results of the study suggest that the initiation and propagation of microdroplets could promote and accelerate marine atmospheric corrosion.